Intensity and Prevalence of Ectoparasites in Common Carp (Cyprinus carpio) fry from Traditional Pond and “Longyam” at Sukamulya Villages, Singaparna, Tasikmalaya - Rustikawati, I.; Rostika, R.; Iriana, D.; Herlina, E. (Indonesian Society of Scientific Aquaculture (ISSA), 2004)
The experiment was done to find out species, intensity and prevalence of common crap fry from traditional ponds and